ANALISIS DASAR HUKUM BAHASA INDONESIA SEBAGAI BAHASA NASIONAL - Neneng Wahyuni (STIH Putri Maharaja, 2018)
This article was written to describe the legal analysis of the Indonesian language as a national language. Indonesian is the language of unity, national language, and national language. The Youth Pledge of the Indonesian Youth Congress on October 28, 1928 was a crystallization of Indonesian nationalism. Indonesian as one of the contents of the youth oath plays an important role for Indonesian nationalism. Indonesian language is a flourishing nationalism in our society that inhabits thousands of islands in the archipelago with various ethnic groups and languages. The language of an area is motivated by different socio-cultural and linguistic backgrounds. Based on this, language will not hamper communication between regions and between cultures, because of the national language or language to avoid misunderstanding with each other due to differences in socio-cultural and linguistic backgrounds. Language as a National language, Indonesian is a dynamic language along with the dynamics of community progress as a result of national development. In order that Indonesian language is used is always good and right, we as speakers of language are required to always be open and dynamic following the development of Indonesian. As an effort to foster Indonesian language, the community must always be positive about Indonesian and Indonesian. Fostering Indonesian language also fosters national nationalism because Indonesian is the national identity of the Indonesian people.